Resection of piriform cortex predicts seizure freedom in temporal lobe epilepsy. Issue 1 (2nd December 2020) - Borger, Valeri; Schneider, Matthias; Taube, Julia; Potthoff, Anna‐Laura; Keil, Vera C.; Hamed, Motaz; Aydin, Gülsah; Ilic, Inja; Solymosi, László; Elger, Christian E.; Güresir, Erdem; Fimmers, Rolf; et al.
Abstract: Objective: Transsylvian selective amygdalo‐hippocampectomy (tsSAHE) represents a generally recognized surgical procedure for drug‐resistant mesial temporal lobe epilepsy (mTLE). Although postoperative seizure freedom can be achieved in about 70% of tsSAHE, there is a considerable amount of patients with persisting postoperative seizures. This might partly be explained by differing extents of resection of various tsSAHE target volumes. In this study we analyzed the resected proportions of hippocampus, amygdala as well as piriform cortex in regard of postoperative seizure outcome. Methods: Between 2012 and 2017, 82 of 103 patients with mTLE who underwent tsSAHE at the authors' institution were included in the analysis. Resected proportions of hippocampus, amygdala and temporal piriform cortex as target structures of tsSAHE were volumetrically assessed and stratified according to favorable (International League Against Epilepsy (ILAE) class 1) and unfavorable (ILAE class 2–6) seizure outcome. Results: Patients with favorable seizure outcome revealed a significantly larger proportion of resected temporal piriform cortex volumes compared to patients with unfavorable seizure outcome (median resected proportional volumes were 51% (IQR 42–61) versus (vs.) 13 (IQR 11–18), P  = 0.0001). Resected proportions of hippocampus and amygdala did not significantly differ for these groups (hippocampus: 81% (IQR 73–88) vs. 80% (IQR 74–92) ( P  = 0.7); amygdala: 100% (IQR 100–100) vs. 100% (IQR 100–100) ( P  = 0.7)). Interpretation: These results strongly suggest temporal piriform cortex to constitute a key target resection volume to achieve seizure freedom following tsSAHE.